The Optimal Nutrition Education for Adolescents At Al Kautsar Junior High School Kartasura - Zulaekah, Siti; Nur Widiyaningsih, Endang; Muwakhidah; Mutalazimah (Abdi Psikonomi, 2025)
Adolescents tend to have poor eating habits that lead to nutritional deficiencies that make them vulnerable to current and future health problems, such as decreased concentration in learning, decreased productivity, and increased risk of comorbidities when they become adults. Teenagers have poor eating behaviors such as consuming foods that are not in accordance with food guidelines, consuming fast food, high-fat foods, sweet drinks, skipping breakfast, and rarely consuming vegetables and fruit. This behavior can be caused by low knowledge, peer influence, parents, increasing fast food centers, mass media and body image. Providing education is very important in increasing the knowledge of adolescents. The purpose of providing this education is to increase the knowledge and awareness of adolescents about the importance of implementing optimal nutrition as an effort to prevent nutritional problems in adolescents.Nutrition optimal education activities for SMP Special Program (PK) Al Kautsar, Junior High School students went well and smoothly according to the schedule. Participants enthusiastically took part in a series of nutrition education activities through animated videos, as well as actively participated in question and answer discussions. This activity received full support from the school to fill in the mentoring activities that are routinely held at PK Al Kautsar Middle School. Nutrition education with optimal nutrition material for adolescents can increase adolescent knowledge by 10.78 points, with an average value of knowledge before being given education of 59.2 and an average value of knowledge after being given education of 70. It is hoped that by increasing knowledge it will improve adolescent food consumption patterns so that good nutritional status can be achieved.